If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = -1x + -18 Reorder the terms: 3 + 2x = -1x + -18 Reorder the terms: 3 + 2x = -18 + -1x Solving 3 + 2x = -18 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 2x + x = -18 + -1x + x Combine like terms: 2x + x = 3x 3 + 3x = -18 + -1x + x Combine like terms: -1x + x = 0 3 + 3x = -18 + 0 3 + 3x = -18 Add '-3' to each side of the equation. 3 + -3 + 3x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = -18 + -3 3x = -18 + -3 Combine like terms: -18 + -3 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| 8-2(3+x)=3(4+x) | | 17x+8y=48+27 | | 6m+8=8m-4 | | 4ab^2-4ab^2= | | 25=.99x+3 | | 8(b+1)-3b=2b-1 | | 17x+8y=48+21 | | 6a-2=2a+8 | | 5x-6-3x+12=10 | | 3x^2+30+21x=0 | | 2xy+1y=10 | | 10r^2+3r+3=0 | | (4t+7)=(2t-55) | | 2xy+-1y=10 | | 14s-5s+30=225 | | 0=14u+32-u^2 | | 6b+2=4b+8 | | 6t-4p= | | 12y+5x=17 | | 80x^2+44x-16=0 | | 5v-6=-41 | | -5y+5(-6+2y)=0 | | 65+(-10+x)=3x+1 | | g(-2)=-2-9 | | 13.7-5.2x=5x-47.5 | | (X-7)=(2x+3) | | (4x+3)+(x-8)=180 | | 8.4-2x=2 | | 4u-6= | | 3(4x-1)=8x+17 | | 15x+21(x-2)=138 | | 3(-3x+6)+10x=8x-17 |